"d‐Electron Complementation" Induced V‐Co Phosphide for Efficient Overall Water Splitting. Issue 38 (1st September 2021) - Zhang, Rui; Wei, Zhenhua; Ye, Gaoyang; Chen, Guanjie; Miao, Jiaojiao; Zhou, Xuehua; Zhu, Xiangwei; Cao, Xiaoqun; Sun, Xiangnan
Abstract: To generate "green hydrogen, " electrochemical water splitting is regarded as the most promising method, which requires highly efficient bifunctional electrocatalysts to accelerate the hydrogen and oxygen evolution reactions (HER and OER). Herein, a "d‐electron complementation" principle to develop such candidates is proposed. By taking advantage of the filling characteristics of 3d orbitals, vanadium‐cobalt phosphide (V‐CoP) is synthesized. According to X‐ray absorption fine structure and X‐ray photoelectron spectroscopy investigation, V can disorder the coordination environment of Co, leading to increased/decreased charge density in Co(P)/Co(O). As a result, V‐CoP shows impressive bifunctional activity, which only needs overpotentials of 46 and 267 mV to deliver 10 mA cm −2 for the HER and OER, respectively. Density functional theory calculations reveal that the accelerated H2 O dissociation process on the VO x /CoO x /CoP surface and H conversion kinetics on the V‐neighboring CoCo bridge site result in promoted HER activity. Furthermore, the up‐shifted d‐band center of V‐CoOOH endows the V‐neighboring Co site with a lowered energy barrier for the OER. This work serves as a proof‐of‐concept for the application of the "d‐electron complementation" principle, which can be a generalized guideline to design and develop novel highly efficient catalysts. Abstract : A "d‐electron complementation" principle is proposed to develop a highly efficient electrocatalyst. As a proof‐of‐concept, V‐Co phosphide is synthesized, which shows V‐determined activity for water splitting. Density functional theory calculations reveal that the high hydrogen evolution reaction activity originates from the charge transfer from V to Co, while the opposite effect is responsible for the high oxygen evolution reaction activity.